2018
DOI: 10.1210/jc.2018-00957
|View full text |Cite
|
Sign up to set email alerts
|

Height as a Clinical Biomarker of Disease Burden in Adult Mitochondrial Disease

Abstract: Context Abnormal growth and short stature are observed in patients with mitochondrial disease, but it is unclear whether there is a relationship between final adult height and disease severity. Objective To determine whether patients with genetically confirmed mitochondrial disease are shorter than their peers and whether stature is related to disease severity. Design Analysis of final adult height in relation to disease severity as determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…It was interesting to note that patients with short stature were more likely to have diabetes and cardiovascular involvement, whereas patients with a low BMI had more severe symptoms such as seizures, encephalopathy, and strokelike episodes, as noted previously (16). Both short stature and low BMI were associated with hearing impairment and gastrointestinal disturbances.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…It was interesting to note that patients with short stature were more likely to have diabetes and cardiovascular involvement, whereas patients with a low BMI had more severe symptoms such as seizures, encephalopathy, and strokelike episodes, as noted previously (16). Both short stature and low BMI were associated with hearing impairment and gastrointestinal disturbances.…”
Section: Discussionsupporting
confidence: 56%
“…The mechanism is believed to be dysfunctional involvement of smooth muscle, peripheral nerves, and central nervous system in swallowing. Gastroparesis, delayed gastric emptying, bacterial overgrowth, and intestinal pseudo-obstruction have also been noted in this population (16). Malabsorption is commonly experienced by patients, and mtDNA defects have been shown to impair human colonic epithelial function (29).…”
Section: Discussionmentioning
confidence: 96%
“…The effect size of these associations are comparable to the top 10% of effects reported for the nuclear genome 24 . Short stature is a well-recognized feature of inherited mitochondrial diseases 25 . In some patients this has a neuroendocrine basis, but this is not the case in most, where impaired cartilage-mediated growth has been implicated 25 , 26 .…”
Section: Resultsmentioning
confidence: 99%
“…In adults, but not in children, genetic severity of disease (GAA1 repeat length) was associated with shorter stature, analogous to a different study in adults with other genetic mitochondrial disorders that showed height was a biomarker of disease burden. 41 The authors posited that primary mitochondrial disorders had subtle effects on growth even before clinical diagnosis. Similarly, the bioenergetic changes related to FRDA may antedate more overt symptoms; therefore, even individuals with adult-onset FRDA may have experienced subclinical effects on growth earlier in life.…”
Section: Discussionmentioning
confidence: 99%